Improved Hydrogenation Kinetics of TiMn(1.52) Alloy Coated with Palladium through Electroless Deposition - Somo, Thabang R. (Materials (Basel), 2021)
The deterioration of hydrogen charging performances resulting from the surface chemical action of electrophilic gases such as CO(2) is one of the prevailing drawbacks of TiMn(1.52) materials. In this study, we report the effect of autocatalytic Pd deposition on the morphology, structure, and hydrogenation kinetics of TiMn(1.52) alloy. Both the uncoated and Pd-coated materials were characterized using scanning electron microscopy/energy dispersive spectroscopy (SEM/EDS) and X-ray diffraction (XRD). XRD analyses indicated that TiMn(1.52) alloy contains C14-type Laves phase without any second phase, while the SEM images, together with a particle size distribution histogram, showed a smooth non-porous surface with irregular-shaped particles ranging in size from 1 to 8 µm. The XRD pattern of Pd-coated alloy revealed that C14-type Laves phase was still maintained upon Pd deposition. This was further supported by calculated crystallite size of 29 nm for both materials. Furthermore, a Sieverts-type apparatus was used to study the kinetics of the alloys after pre-exposure to air and upon vacuum heating at 300 °C. The Pd-coated AB(2) alloy exhibited good coating quality as confirmed by EDS with enhanced hydrogen absorption kinetics, even without activation. This is attributed to improved surface tolerance and a hydrogen spillover mechanism, facilitated by Pd nanoparticles. Vacuum heating at 300 °C resulted in removal of surface barriers and showed improved hydrogen absorption performances for both coated and uncoated alloys.